Vegetation responses to late Holocene climate changes in an Andean forest. Issue 1 (7th September 2017) - Schiferl, Jacob D.; Bush, Mark B.; Silman, Miles R.; Urrego, Dunia H.
Abstract: A paleoecological record from Lake Palotoa (1370 m elevation) in the Andean foothills of Peru spans the last 3800 years. Lake Palotoa lies near the modern cloud base in a location sensitive to changes in atmospheric moisture. In many areas, these forests have been destroyed, but Lake Palotoa shows no sign of human occupation today or in the past. The modern forest surrounding the lake is dominated by the Andean palm, Dictyocaryum lamarckianum, which is also the most abundant taxon in the fossil pollen record. Fossil pollen data show the vegetation assemblages have not experienced strong compositional changes in the late Holocene. Global-scale climatic events such as the Medieval Climate Anomaly (MCA) and the Little Ice Age (LIA) are identified within the record, though the vegetation responses are subtle. Hedyosmum and Sloanea pollen percentages increase near the onset of the MCA and may reflect decreased seasonality. The LIA coincides with increased Hedyosmum pollen percentages, and increases in Clethra and Begonia, two elements that tend to occupy forests now found at higher elevations. Our findings demonstrate the stability of montane forest systems to natural Holocene climate change.